YOUTH - unidad de investigación del cacao y del arroz (2020)
This document illustrates a comprehensive solutions approach to the problems diagnosed in the Santander and Cesar region, in Colombia. Likewise, it aims to show strategies used through research, consultation and subsequent diagnosis of the different structures that make up the regions. The work is done in order to improve the conditions and quality of life of the population.